Building Systems for Universal Health Coverage in South Korea - Na, Sanggon; Kwon, Soonman (World Bank, Washington, DC, 2015)
This paper broadly examines the development process of Korea’s health care system toward the achievement of Universal Health Coverage. Korea implemented a series of health care reforms after a rapid expansion of population coverage to improve efficiency and equity in financing and delivery of health care. The authors also investigate changes in the governance structure of Korea’s national health Insurance, which is now represented by two agencies: National Health Insurance Service (NHIS) and Health Insurance Review and Assessment Service (HIRA). Health insurance agencies have improved the accountability and transparency of the health insurance system, thanks to the ICT-based centralized claim review and assessment. Lessons and challenges from Korea’s experiences and achievements on the road to UHC could provide valuable policy implications to low- and middle-income countries.